Cultural activities in primary school students' spare time - Mikanović Brane; Panzalović Slavojka (Sinteze, 2014)
Culture is a form of creative expression of a human being through which he reshapes the world, acts on it adding it value and creating new, cultural values. A human being is able to create a product of culture only when he is free and able to express himself. A contemporary man can incorporate various cultural activities into his spare time. They are especially important when they concern children and young people: regardless of whether they are used in institutional settings or in spare time. The authors conducted an empirical research of students' assumptions and beliefs concerning cultural activities in their free time. The sample comprised 233 fifth grade students. The findings show that in their spare time fifth graders: engage in various cultural activities; that students who live in urban areas attend more cultural events; that students have the opportunity to engage in extra-curricular activities in the area of culture - join cultural and artistic groups and associations and engage in various creative pursuits at different levels of participation (as consumers, full participants); and that students' attitudes concerning the influence of parents and teachers on the selection of cultural activities to be pursued do not vary greatly by gender, location or school achievement. Cultural activities do play a significant part in the free time of primary school students. This is why it is important that guidance provided in school and in spare time should be brought in greaer harmony.